Expression of dopamine and vesicular monoamine transporters and differential vulnerability of mesostriatal dopaminergic neurons - González-Hernández, Tomás; Barroso-Chinea, Pedro; de la Cruz Muros, Ignacio; del Mar Pérez-Delgado, María; Rodríguez, Manuel (Journal of comparative neurology (1911), 2004)
Numerous studies suggest that the dopamine transporter (DAT), responsible for dopamine reuptake, may act as a vulnerability factor in the pathogenesis of Parkinson's disease (PD) and the vesicular monoamine transporter (VMAT2), responsible for its vesicular storage, as a neuroprotective factor. However, the relevance of each on the differential vulnerability of midbrain DA cells remains uknown. Here we studied the relationship between the expression pattern (mRNA and protein) of both transporters and the differential vulnerability of midbrain DA cells in a model of PD (intracerebroventricular injection of 6‐OHDA in rats) and in monkey and human midbrain. Our results revealed that the expression patterns for VMAT2 mRNA and protein and DAT mRNA are similar, with the highest levels in the rostromedial region of substantia nigra (SNrm), followed by the caudoventral region of SN (SNcv), the ventral tegmental area and pigmented parabrabraquial nucleus (VTA/PBP), and finally the linear and interfascicular nuclei (Li/IF). In contrast, the expression of DAT protein in rats, monkeys, and humans followed a caudoventrolateral‐to‐rostrodorsomedial decreasing gradient (SNcv > SNrm > VTA/PBP > Li/IF), matching the degeneration profile observed after intracerebroventricular injection of 6‐OHDA and in PD. In addition, DAT blockade made all midbrain DA cells equally resistant to 6‐OHDA. These data indicate that DAT protein levels, but not DAT mRNA levels, are closely related to the differential vulnerability of midbrain DA cells and that this relationship is unaffected by the relative levels of VMAT2. Furthermore, the difference between DAT mRNA and protein profiles suggests internuclear differences in its posttransductional regulation. J. Comp. Neurol. 479:198–215, 2004. © 2004 Wiley‐Liss, Inc.